Basic geometry skills VLOKS model and alternative learning methods for prospective elementary school teachers in Khatulistiwa City - Bistari; Rustam; Fitriawan, Dona; Winarji, Agus (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: Prospective elementary teachers often experience difficulty connecting visual representations with conceptual understanding, resulting in fragmented reasoning about geometric properties. This study aims to examine pre-service teachers’ geometric reasoning using the VLOKS model, with a specific focus on the visual and literal dimensions that frequently hinder the transition from perceptual recognition to conceptual comprehension. Method: A descriptive qualitative design was implemented involving 199 students from the Primary Teacher Education Program at Universitas Tanjungpura. Data were collected through a 12-item diagnostic test, semi-structured interviews, participatory observations, and focus group discussions. Thematic analysis was conducted through data reduction, display, and verification, supported by triangulation of methods and sources to ensure credibility in interpreting students’ visual, literal, operational, correlational, and spatial reasoning processes. Findings: The study found that students’ visual reasoning was largely limited to surface-level recognition of shapes, with little progression toward analytical interpretation. Literal reasoning showed substantial difficulty, particularly in translating verbal descriptions into accurate geometric representations. While operational skills appeared moderately developed, correlational reasoning and spatial visualization were relatively weak, indicating that students struggled to integrate multiple geometric ideas into coherent conceptual structures. Significance: The results underscore that pre-service teachers’ geometric reasoning remains predominantly visual and descriptive, lacking depth in relational and representational understanding. The VLOKS model offers a systematic framework for diagnosing these reasoning gaps and guiding pedagogical interventions. Strengthening the visual and literal dimensions through multi-representational learning, contextual visualization, and reflective reasoning can enhance conceptual understanding and improve teacher readiness in geometry instruction